The Illocutionary Act as a Verbal Weapon : An Analysis of Cyberbullying in Bhad Bhabie’s ‘Ms. Whitman’ - Radita Astried Rizkya; Vinjellina Batubara; Sophie Meilatifah; Trivera Hana; Dian Marisha Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
Here, it is examined how language is employed as a weapon on the internet by means of the illocutionary acts in Bhad Bhabie's 2023 diss track